Oviposition and survival in females of Procornitermes araujoi under laboratory conditions (Isoptera, Termitidae, Nasutitermitinae) - Costa-Leonardo, Ana Maria [UNESP]; Soares, Helena Xavier [UNESP] (My University, 1997)
After an enormous swarming of Procornitermes araujoi when a great number of females were collected, we investigated the occurrence of parthenogenesis beyond oviposition and survival of these females under laboratory conditions. The groups of virgin females were faster in their first oviposition than females of male-female pairs, nevertheless their eggs never hatch. The survival data showed higher longevity in the group of three females when compared with groups of two and four females.
Keywords: Oviposition; Procornitermes araujoi; Survival; Termitidae